LANGUAGE, MEANING, CULTURE IN INTERNATIONAL PUBLIC RELATIONS - Albu, Ioana (European Scientific Journal, ESJ, 2013)
The present paper aims at tackling the issue of international public relations from a cultural studies perspective, having in mind the cultural specificity, given the variety of forms of public relations in the world. The public relations field has evolved all over the world with increased intensity nowadays, having become a genuine ‘global industry’, covering countries with extremely varied cultures, political systems and development. With a wide span across the globe, from the US to Asia and lately Africa, from Ireland to Russia and Eastern Europe, this field has evolved fast, based on the creation of institutional structures that define the way in which the public relations work and legitimate themselves. It is an ascertained fact that the public relations have become a significant ‘business’ at a global level, with an increased development, faster than that of the global economy on the whole. According to the PR data base, in Romania there are around 40 public relations agencies nowadays, compared to only one in 1992[public-relations.ro] The present paper focuses on the fundamental aspects of the public relations activity, in an attempt at showing the way they are practiced around the world, highlighting the importance of culture in any activity of international public relations. From the very wide references in the field, the approach illustrated by Curtin, P. & Gaither,K. was a highly valued source of understanding and reinterpreting phenomena in the field, as well as the articles offered by various international public relations associations in the country and abroad.